(untitled) (Research, Society and Development, 2024)
Currently, a large number of substances are found in the aquatic environment, with pharmaceuticals, mainly the anti-inflammatory class, found in this environment. Due to the large number of drugs with toxic potential for aquatic organisms, it is necessary that ecotoxicological studies be carried out to evaluate the impacts of these substances. The objective of this work was to evaluate the growth of the green alga Chlorella vulgaris when exposed to anti-inflammatories and paracetamol in different concentrations, observing the behavior of algal growth in acute exposure of 5 days and chronic exposure of 30 days. Growth assessment was performed through direct counting by microscopy. The results obtained demonstrated that acute exposure to Paracetamol at different concentrations inhibited the growth of C. vulgaris with statistically significant results with an effect on 50% of the organisms exposed under the tested conditions, indicating a negative effect on microalgae. In relation to chronic exposure, Nimesulide at concentration NM3 caused cell growth of C. vulgaris superior to the control by 21,16% and Paracetamol at concentrations P2 and P3, inhibited the growth of C. vulgaris by 30,88% and 31,54%, respectively, effects with results that presented statistical significance, indicating a negative effect on microalgae. For results obtained without statistical significance in acute and chronic exposure to medicines, the toxic potential for the organism tested cannot be ruled out, and further studies with different exposure conditions are necessary.